2005
DOI: 10.1152/japplphysiol.00788.2004
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen’s attenuating effect on the exercise pressor reflex is more opioid dependent in gonadally intact than in ovariectomized female cats

Abstract: Schmitt, Petra M., and Marc P. Kaufman. Estrogen's attenuating effect on the exercise pressor reflex is more opioid dependent in gonadally intact than in ovariectomized female cats. J Appl Physiol 98: 633-639, 2005. First published September 24, 2004 doi:10.1152/ japplphysiol.00788.2004.-Using gonadally intact female cats, we showed previously that estrogen, applied topically to the spinal cord, attenuated the exercise pressor reflex. Although the mechanism by which estrogen exerted its attenuating effect is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(42 reference statements)
3
8
0
1
Order By: Relevance
“…Furthermore, in agreement with the results of Jarvis et al (28), the present findings may also not depend on estrogen per se, as these experiments were performed in the early follicular phase of the menstrual cycle, where estrogen is at low levels, similar to that of men (15,21,56). Schmitt et al (53) indicated that, while the exercise pressor reflex can be suppressed by estrogen, there appears to be cross-talk between the estrogen and opioid systems, suggesting an indirect effect of estrogen. Therefore, in combination, the results from present and previous studies suggest that through either direct or indirect mechanisms, the presence of estrogen and/or other factors associated with being female appear to blunt both group III (mechanosensitive) and group IV (metabosensitive) afferent feedback and subsequent cardioacceleration.…”
Section: Sex Specificity In Central Hemodynamicssupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, in agreement with the results of Jarvis et al (28), the present findings may also not depend on estrogen per se, as these experiments were performed in the early follicular phase of the menstrual cycle, where estrogen is at low levels, similar to that of men (15,21,56). Schmitt et al (53) indicated that, while the exercise pressor reflex can be suppressed by estrogen, there appears to be cross-talk between the estrogen and opioid systems, suggesting an indirect effect of estrogen. Therefore, in combination, the results from present and previous studies suggest that through either direct or indirect mechanisms, the presence of estrogen and/or other factors associated with being female appear to blunt both group III (mechanosensitive) and group IV (metabosensitive) afferent feedback and subsequent cardioacceleration.…”
Section: Sex Specificity In Central Hemodynamicssupporting
confidence: 93%
“…The results from Jarvis et al (28) suggest that the sex differences during hand- In support of this reduced afferent signaling in women, the present findings suggest that women display attenuated group III afferent nerve or mechanoreceptor sensitivity, as evidenced by a lower CO response to passive limb movement. Although the mechanism responsible for this attenuation was not elucidated in the present study, previous work (51)(52)(53)(54) performed using an animal model has determined that estrogen, either endogenously or via spinal application, can attenuate the exercise pressor reflex in both male and female rats. This implies a significant role of estrogen in modulating afferent nerve signaling and the subsequent exercise pressor reflex (51)(52)(53)(54).…”
Section: Sex Specificity In Central Hemodynamicsmentioning
confidence: 73%
See 1 more Smart Citation
“…Antagonists included the broad-spectrum opioid receptor antagonist naloxone (1, 10, 25 mM; n  = 6, 4, 4 animals each, respectively), the mu-specific opioid antagonist beta-funaltrexamine (1, 10 mM; n  = 4 each), and the kappa-specific opioid antagonist nor-binaltorphimine (0.66, 6.6 mM; n  = 3 each). Drug doses were based on previous studies of opioid–steroid interactions (Evans et al 2000; Acosta-Martinez and Etgen 2002; Ceccarelli et al 2004; Schmitt and Kaufman 2005). The standard dose sequence (1, 10 mM) was lowered slightly for nor-binaltorphimine due to limited reagent availability; it is an effective kappa-opioid antagonist in both mammalian and non-mammalian vertebrates (Bradford et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…However, another study failed to demonstrate any significant differences in the maximal elongation or stiffness of the patellar tendon across the menstrual cycle (22). It also appears that these hormones might have neurosteroidal effects that can potentially alter neural transmission through the peripheral nervous system, spinal cord and brain (32, 37). In light of the potential for female sex hormones to modulate connective tissue mechanics and neural circuitry, a handful of studies have investigated changes in motor control throughout the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%